Nyongkolan Tradition of The Sukarara Indigenous People of Lombok Middle In A Comparative Approach To Legal Anthropology - Surya Kusuma Wardana; Suparno Suparno; Emy Handayani (Green Publisher Indonesia, 2023)
The Nyongkolan tradition of the Sukarara Central Lombok community can last a long time as a crystallization of noble habits in the implementation of the Nyongkolan tradition which is accepted as a custom of the Sukarara Central Lombok community and its imp lementation is supported by legal protection in comparative studies of legal anthropology in accommodating the preservation of the Nyongkolan tradition from extinction, a tradition which is the guardian of the Nyongkolan tradition preservation. The Nyongkolan tradition in the study of a comparative approach is to compare one regulation with the reality that occurs in the Sukarara Central Lombok community through the Marriage Law no. 1 / 1974, so that nyongkolan marriage or traditions as traditions related to the authority in determining custom system of Sukarara village, Jongat district, Central Lombok. The theory used by the researcher in this study is the theory of Cultural Relativism which views local wisdom as a tradition, addressing the reality of plurality and religion through understanding the traditions and culture of the community in maintaining traditions in the local wisdom of the indigenous Sukarara Central Lombok community. The suggestion used in this study, the government of West Nusa Tenggara Province should synergize with the reality that occurs in the indigenous Sukarara Central Lombok community while maintaining local wisdom of the local indigenous people